2017
DOI: 10.3389/fphys.2017.00904
|View full text |Cite
|
Sign up to set email alerts
|

GMSC-Derived Exosomes Combined with a Chitosan/Silk Hydrogel Sponge Accelerates Wound Healing in a Diabetic Rat Skin Defect Model

Abstract: Background: Delayed wound healing in diabetic patients is one of the most challenging complications in clinical medicine, as it poses a greater risk of gangrene, amputation and even death. Therefore, a novel method to promote diabetic wound healing is of considerable interest at present. Previous studies showed that injection of MSC-derived exosomes has beneficial effects on wound healing. In current studies, we aimed to isolate exosomes derived from gingival mesenchymal stem cells (GMSCs) and then loading the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
254
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(258 citation statements)
references
References 50 publications
3
254
0
1
Order By: Relevance
“…However, growth factors rapidly degrade in vivo, and therefore, we needed a suitable delivery vehicle to maintain the biologic activity and bioavailability of growth factors, transport them safely to the wound, and control their release. A previous report revealed that exosomes combined with a chitosan or silk hydrogel can accelerate wound healing in diabetic rats (39), and our previous studies confirmed that growth factor and hydrogel combinations, such as heparin-FGF2@PEAD coacervate (40) and HP-FGF2 (24), can greatly promote skin wound healing in normal mice. HP is a thermosensitive hydrogel micelle material composed of poloxamer 407 and heparin combined via a polycondensation reaction.…”
Section: Discussionsupporting
confidence: 73%
“…However, growth factors rapidly degrade in vivo, and therefore, we needed a suitable delivery vehicle to maintain the biologic activity and bioavailability of growth factors, transport them safely to the wound, and control their release. A previous report revealed that exosomes combined with a chitosan or silk hydrogel can accelerate wound healing in diabetic rats (39), and our previous studies confirmed that growth factor and hydrogel combinations, such as heparin-FGF2@PEAD coacervate (40) and HP-FGF2 (24), can greatly promote skin wound healing in normal mice. HP is a thermosensitive hydrogel micelle material composed of poloxamer 407 and heparin combined via a polycondensation reaction.…”
Section: Discussionsupporting
confidence: 73%
“…(Table 1). Various investigations suggested that gingival MSC-derived EXs, EVs, or CM could represent novel therapeutic interventions in managing peripheral nerve injury [168,169], motor neuron injury [170], and skin [171] and bone defects [172]. The results were comparable with effects conferred by direct transplantation of gingival MSCs [168,169].…”
Section: Gingival Mesenchymal Stem/progenitor Cell-derived Secretome/mentioning
confidence: 99%
“…The implementation of gingival MSC-derived EXs in skin repair proved to be of practical value. Isolated EXs with an average diameter of 127 nm derived from gingival MSCs loaded on chitosan/silk hydrogel sponge effectively promoted healing of skin defects in diabetic rats detected by the formation of neoepithelium and collagen as well as a rise in the microvessels' number detected by CD34 in the wound 17 Stem Cells International bed and neuronal ingrowth detected by neurofilament heavy chain (NEFH), two weeks postsurgery [171]. (Table 4).…”
Section: Gingival Msc-cm In the Therapy Of Neural Disordersmentioning
confidence: 99%
“…In an acute lung injury mouse model, a single intravenous administration of SHED-secreted factors alleviated lung injury, weight loss, and inflammatory response, accompanied by an increased number of anti-inflammatory M2-like lung macrophages [100]. GMSC-derived exosomes were capable of accelerating wound healing in diabetic mice by promoting reepithelialization, angiogenesis and neuronal ingrowth, and collagen remodeling [109]. Particularly, exosomes derived from healthy BM-MSCs alleviated radiation-induced bone loss by recovering the adipogenic and osteogenic differentiation potential of radiation-injured BM-MSCs via Wnt/β-catenin activation [110].…”
Section: Oral Msc-derived Extracellular Vesicles (Evs) In Conditionedmentioning
confidence: 99%